Incorporating Effective Electronic Gadgets into the Students’ Learning in ODeL Academic Landscape Experiences - Netanda, Rendani Sipho (Journal of Teaching and Learning, 2024)
The use of e-gadgets for instructional practices, learning processes, and bridging transactional distance between higher-educational institutions and students remain complex and contested phenomena in educational research. However, studies that were grounded on the mixture of the Replace-Amplify-Transform (RAT) model and Acceptance and Use of Technology2 (UTAUT2) to study the impact of e-gadgets in an Open Distance e-Learning-landscape (ODeL) are still scant. This inquiry sought to find answers to the question: How does using e-gadgets impact a students’ learning experience? The purpose of this study is to enhance an understanding of students’ experience with e-gadgets for learning. Data were generated using in-depth interviews with students, employing thematic analysis as a methodological orientation. Findings unveiled that many rural-based students have no access to e-gadgets, which has an influence on performance, success, and retention rates. Findings further demonstrate that effective e-gadgets are significant in ODeL students’ learning trajectory. Reliance on e-gadgets leads to dependency and deters innovation, as learners tend to over rely on readily available resources. Institutions must expand access to e-gadgets to help students complete their studies within the prescribed duration. For ODeL institutions to bridge transactional distance, access to e-gadgets must be expanded.